Study of urinary shedding and identification of chronic carriers of pathogenic leptospires in dogs kept in public or private animal shelters of metropolitan São Paulo area - Miotto, Bruno Alonso (2016)
Leptospirosis is a zoonotic disease of global importance caused by pathogenic Leptospira species. Dogs are reservoir hosts for pathogenic Leptospira and can act as potential transmission sources of the disease. Identification of such individuals and characterization of leptospires involved in chronic infections may promote a better understanding of the role of dogs in the epidemiology of particular leptospiral strains and the overall contribution of dogs to environmental contamination in urban and rural scenarios. The present work describes the identification of dogs presenting asymptomatic urinary shedding of different pathogenic Leptospira species among stray and sheltered dog populations, as well as the characterization of leptospiral strains isolated from chronic carriers. Blood and urine samples were taken from three different populations: (I) 92 dogs kept in a public shelter at the University of São Paulo campus; (II) seven stray dogs living inside the University of São Paulo campus; and (III) 24 dogs kept in a public shelter from the city of Mogi das Cruzes. Dogs identified as urinary shedders by PCR-based DNA detection were prospectively evaluated in order to confirm persistent renal carriage of the pathogen and to recover viable leptospires for proper characterization. Leptospiruric dogs were identified in all populations studied. Quantitative PCR targeting the lipL32 gene and the 16S rRNA detected urinary shedding in 10 dogs (10,87%) from population I: two of these dogs were recently admitted at the facility and one dog was adopted immediately after presenting large quantities of leptospires in urine. Prospective evaluation of nine leptospiruric dogs enabled the identification of two chronic carriers, allowing the recovery of leptospires from both dogs. The strains were further characterized by MLST analysis and serogrouping, thus confirming infection caused by L. interrogans serogroup Canicola and L. santarosai serogroup Sejroe. Two leptospiruric dogs (28,5%) were detected in population II by 16S and secY PCR amplification; one dog presented persistent urinary shedding of L. interrogans, but no isolates could be recovered. The other leptospiruric dog presented asymptomatic infection caused by L. santarosai and could not be reevaluated. Only one dog from population III (4,1%) presented leptospiruria detected by PCR; the dog could not be reevaluated, however sequence analysis revealed infection caused by L. santarosai. The results indicate the first report of L. santarosai infection in dogs. Asymptomatic infection caused by this leptospiral species was observed in all populations studied, thus indicating a possible role of dogs in the chain of transmission of this particular pathogen. The results also suggest a possible genetic distinction between lineages of Brazilian L. santarosai maintained by dogs and other animal hosts. Isolation and persistent chronic carriage of L. santarosai found shows that dogs can persistently harbor leptospires other than L. interrogans. This study also points out that dogs can be inadvertently admitted and adopted in dog shelters, potentially increasing the risks of occupational and zoonotic transmission by bringing infected animals closer to shelter workers, adopters and their households.